Evaluasi Pembelajaran Daring Melaui Media E-Learning di Masa Pandemi Covid-19 pada Mata Kuliah Fisiologi Olahraga - Rika Sepriani; Ambiyar Ambiyar; Ishak Aziz (Pusat Kajian Pendidikan Olahraga Kesehatan Rekreasi, 2021)
The problem in this study is that there has not been an evaluation of online learning through e learning during the Covid-19 pandemic in the Sports Physiology course. For this reason, this study aims to determine the achievement of online learning that has been carried out until mid-semester as a form of learning evaluation. In this study, the sample was obtained from students who took the Sports Physiology lecture who met the inclusion criteria as many as 58 people. This type of research is a quantitative descriptive study using two methods, survey methods namely in the form of a questionnaire to determine the ability of students to access e learning and an essay test to determine student learning outcomes until mid-semester, especially in the cognitive aspects. The results showed that students had been able to access e learning well and had a good average value of learning outcomes.